Breathing and Light- to Vigorous-Intensity Aerobic Exercises Improved Respiratory Functions and Functional Capacity of COVID-19 Survivor with Morbid Obesity - Arnengsih Nazir; Agung Budi Sutiono (Jurnal Respirasi, 2023)
Introduction: A decrease in respiratory functions (RF) and functional capacity (FC) may present as complications of intensive care unit (ICU) admission. Morbid obesity worsens these complications. Case: A 31-year-old male patient with morbid obesity came for pulmonary rehabilitation (PR) one week after hospitalization. He suffered from COVID-19 and received 15 days of mechanical ventilation. The goal of PR was to improve RF and FC. A comprehensive PR, including hospital- and home-based programs, consisting of breathing, aerobic, resistance, and flexibility exercises, diet and psychological counseling was given. Breathing exercises were deep breathing, sustained-maximal breathing, and chest expansion. Hospital-based PR was given with moderate-intensity interval aerobic exercise (AE), while home-based PR was with low-intensity continuous, both with oxygen supplementation. The FC was needed to do his daily activities, and vocational was 1.0 to 6.3 metabolic equivalents (METs). The target of FC 6 METs in 12-18 weeks was set. After six weeks, the RF improved with decreased dyspnea and increased maximum inspiratory volume and chest expansion. The FC increased to 4.2 METs, and monitored-home-based AE was given with vigorous-intensity interval mode. He joined the residency program 10 weeks later and achieved 5.7 METs at the end of PR. We gave unsupervised home-based exercises for his long-term exercise. Conclusion: Breathing and AE improved RF and FC in a COVID-19 patient with morbid obesity admitted to the intensive care unit (ICU) to previous vocational activities.